The influence of brand image promotion and product quality on the purchase decision of hammerstout products - Wlfrin Nando Sanjaya; Andhi Sukma (Enrichment : Journal of Management, 2023)
This study examines the level of purchasing decisions of Hammerstout Products. The urgency of this study raises a problem that occurred to Hammerstout. Consumer purchasing decisions on a product will also be obtained from marketing. A marketing there is a marketing mix that will distribute or combine marketing activities to increase sales of products or services. Therefore, research is conducted to increase sales by combining various marketing activities at one time. This study aims to analyze brand image, promotion and product quality on the purchase decision of Hammerstout Products. The research method used is quantitative research method. The population in this study was all consumers of Hammerstout Products. Sampling is done by Probability Sampling technique. The number of samples was determined as many as 100 people. The primary data collection method used is to use the distributed questionnaire media. The statistical test used is multiple linear regression. Research shows that brand image, promotion and product quality influence the purchase decision of hammerstout products with an influence of 80.5% in a positive direction, which is dominated by promotion and the remaining 19.5% is explained by other factors that are not studied.